Public Sector Development on Human Capital through Fitted Management - Sihombing, Haeryip; Yaakob, Mohd Yuhazri; Safarudin, Mochamad (STIA LAN Press, 2011)
The success of economic and social development depends on the competence, good governance, and public sector functions. However, in reality the practices of centralized policies for public services in most developing countries become the barrier to the effective provision of public services in the global competition. This is especially related to people and organization development in public institutions. The purpose of this paper is to review challenges faced by public sector and to seek for the solutions based on concept integration, implementation, and performance measurement of their business. The proposed conceptual framework is Fitted Management, where the exploration of organization processing capabilities and how to manage it (to be consistent with the globalization) based on the premise of what constitutes a customer value in the public sector by improving the ability of employees and organizations.